Determination of Learning Needs of Patients Undergoing Total Knee Replacement Surgery at Discharge - Emel Ceyhan; Hande Cengiz Açıl (Sakarya Tıp Dergisi)
Introduction: This study was planned to determine the learning needs of patients who underwent total knee replacement (TKR) surgery at discharge. Materials and Methods: The research sample consisted of 60 patients aged 18 and over who had undergone total knee replacement surgery in the orthopedic service of a Training and Research Hospital and agreed to participate in the study. Patients were interviewed in the postoperative period using the Personal Data Form and the Patient Learning Needs Scale (PLNS). Results: The average age of the patients who underwent surgery was 65.03±6.88 and the average BMI was 29.58±3.52. While the average length of hospital stay (days) was 5.30±1.69, 78.3% were women and 88.3% underwent spinal anesthesia. All patients and caregivers received discharge training on home care. The patient PLNS score is 168.90±32.34.It was observed that the highest importance level score among the patients’ scale subgroups was treatment and complications. Conclusions: The learning needs of the patients were found to be moderately important. It was determined that the importance levels of patient education needs were higher for those with spinal anesthesia, those with primary school education or higher, those who were single, and those whose income was less than their expenses. It was observed that the importance levels of the feelings about the situation and treatment complications subdimensions of the PLNS were higher in those who had not had surgery before than in those who had surgery.